THE EFFECTIVENESS OF KIDS SURVIVOR PROGRAM IN DEVELOPING CHILDREN’S CHARACTERS - Hanna Amalia; Syarifah Zainab; Maria Ulfa (Psikoislamedia : Jurnal Psikologi, 2021)
Strengthening and building character must start from an early age. Character education, both formal and informal, is one way to build quality human character. The purpose of this study is to provide an alternative method of developing and strengthening children's character through nature activities in the Kids Survivor program. Mix Method (quantitative and qualitative) was used to determine the effectiveness of the Kids Survivor program. Based on the test, it was found that each subject had an increased score from before participating in Kids Survivor. Every child experienced improvement in every aspect of character. The conclusion of this study is that activities like the Kids Survivor Program contribute to the formation of children's characters. Each child displayed different scores in changes in aspects of character caused by parenting factors and values believed in the family which had been obtained before joining the program. Parenting patterns, experiences throughout a child's development, as well as values that are believed and planted since childhood will slowly shape the child's character.